Instrument to screen cases of pervasive developmental disorder: a preliminary indication of validity Instrumento para rastreamento dos casos de transtorno invasivo do desenvolvimento: estudo preliminar de validação - Fábio Pinato Sato; Cristiane Silvestre Paula; Rosane Lowenthal; Eduardo Yoshio Nakano; Décio Brunoni; José Salomão Schwartzman; Marcos Tomanik Mercadante (Brazilian Journal of Psychiatry, 2009)
OBJECTIVE: To translate into Portuguese, back-translate, culturally adapt and validate a screening instrument for pervasive developmental disorder, the Autism Screening Questionnaire, for use in Brazil. METHOD: A sample of 120 patients was selected based on three groups of 40: patients with a clinical diagnosis of pervasive developmental disorder, Down syndrome, or other psychiatric disorders. The self-administered questionnaire was applied to the patients' legal guardians. Psychometric measures of the final version of the translated questionnaire were tested. RESULTS: The score of 15 had sensitivity of 92.5% and specificity of 95.5% as a cut-off point for the diagnosis of pervasive developmental disorder. Internal validity for a total of 40 questions was 0.895 for alpha and 0.896 for KR-20, ranging from 0.6 to 0.8 for both coefficients. Test and retest reliability values showed strong agreement for most questions. CONCLUSIONS: The final version of this instrument, translated into Portuguese and adapted to the Brazilian culture, had satisfactory measurement properties, suggesting preliminary validation proprieties. It was an easy-to-apply, useful tool for the diagnostic screening of individuals with pervasive developmental disorder. OBJETIVO: Tradução, retro-versão, adaptação cultural e validação do Autism Screening Questionnaire para a língua portuguesa e para o seu uso no Brasil. MÉTODO: Foi selecionada uma amostra inicial de 120 pacientes, encaminhados de duas clínicas privadas e uma pública, divida em três grupos de 40 pacientes distintos: pacientes com diagnóstico clínico de transtornos globais do desenvolvimento ou transtornos invasivos do desenvolvimento; de síndrome de Down e de outros transtornos psiquiátricos. O questionário foi aplicado aos responsáveis legais dos pacientes seguindo os padrões de um questionário auto-aplicável. As medidas psicométricas do questionário traduzido, na sua versão final, foram testadas. RESULTADOS: Valores de sensibilidade de 92,5% e especificidade de 95,5% foram encontrados para uma pontuação de 15, como sendo um valor discriminativo para os sujeitos com características de transtornos globais do desenvolvimento/transtornos invasivos do desenvolvimento. A validade interna para o total das 40 questões foi de 0,895, com uma variação entre 0,6 a 0,8. Os valores de confiabilidade obtidos pelo teste e re-teste demonstraram que a maioria das questões obteve alta concordância. CONCLUSÕES: A versão final do instrumento de pesquisa, traduzido e adaptado à cultura brasileira, apresentou propriedades de medida satisfatórias, sugerindo adequadas propriedades preliminares de validação. É um instrumento de fácil aplicação e uma ferramenta útil para a realização de um screening diagnóstico em indivíduos com transtornos globais do desenvolvimento/transtornos invasivos do desenvolvimento.